Evaluating the Efficacy of Topical Tranexamic Acid in Neck Dissection to Reduce Post-Operative Drain Output: a Randomized Controlled Trial - Imran, Muhammad Azhar; Chatha, Asad Aizaz; Manzoor, Hafiz Muhammad Jawaad; Sohail, Mannal; Nasim, Muhammad Bin; Pasha, Muhammad Ahmed (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To assess efficacy of topical “tranexamic acid (TXA)” in neck dissection to reduce drain output. Study Design: Randomized Controlled Trial (IRCT 20231019059765N1). Place and Duration of Study: Oral & Maxillofacial Surgery Department of CMH, Lahore Medical College & Institute of Dentistry, Lahore Pakistan, from Aug 2023 to Mar 2024. Methodology: Fifty patients who were scheduled to undergo “supraomohyoid neck dissection” due to malignancy of oral cavity, head or neck were included in the study and were divided into “TXA Group” and “control Group”. Drain output, intraoperative and post-op parameters were assessed and compared between Groups. Data was analyzed by SPSS 22.00. Results: Median age was 53.00 (81.00 – 25.00) years. There were 38(76.00%) males and 12(24.00%) were females. Mean drain output in “TXA Group” was 194.56±25.47ml while in “control Group” it was 301.48±49.53ml, (p<0.001). Mean duration of drain removal in “TXA Group” was 5.08±0.99 days while in “control Group” it was 8.72±2.18 days, (p<0.001). Conclusion: Topical “TXA” effectively reduces drain output after neck dissection.